The significant role of sediment bio-retexturing within a contemporary carbonate platform system: Implications for carbonate microfacies development - O'Leary, Mick; Perry, C.; Beavington-Penney, S.; Turner, J. (Elsevier Science BV, 2009)
Assessments of carbonate platform reef–lagoon sediments and benthic habitats around Rodrigues Island (south-west Indian Ocean) have been undertaken in order to examine carbonate sediment texturalproperties and the controls on texturally-defined sediment fabrics. Reef–lagoon sediments, sampled from across the expansive (~8 km wide) carbonate-dominated windward platform, principally comprise poorly sorted medium- to coarse-grained bioclastic sands, composed of a low diversity of grain constituents — predominantly non-geniculate coralline algal bioclasts. Despite a marked homogeneity in sediment compositional and grain size properties, eight distinct sediment textural groups can be identified that form a heterogeneous mosaic across the contemporary reef–lagoon system. Only along the narrow outer platform margins (reef crest, sand apron and outermost lagoon environments) do we observe consistent (predictable) transitions in sediment textural groups, where physical processes are the primary drivers of selective sediment transport and sorting. In contrast, across the main expanse of the lagoon, the sediment substrates are characterised by an irregular mosaic of texturally-defined sediment groups — formed primarily as a function of sediment bio-retexturing. The burrowing activities of alpheid and callianassid shrimps are particularly important in this respect and impart a distinctly unique textural fabric to the upper sediment horizons in the environments in which the respective organisms occur. The consequence of this is that, at the platform system scale, individual, texturally-defined sediment groups are relatively poor indicators of prevailing hydrodynamic regimes or of local sediment production, reflecting more the biological action of organisms inhabiting the substrate. This has important implications for understanding the development of carbonate sediment fabrics in the context of palaeoenvironmental reconstructions and for interpreting a key diagnostic criteria of carbonate microfacies